Desentralisasi Fiskal, Tax Effort dan Pertumbuhan Ekonomi: Studi Empirik Kabupaten/Kota di Indonesia 2001-2008 - Priyarsono, D. S.; Budiasih, Budiasih; Agustina, Neli (Jurnal Ekonomi dan Pembangunan Indonesia, 2010)
Indonesia has implemented a new policy of regional autonomy and fiscal decentralization for almost ten years. One of the objectives of this fiscal decentralization is to give the full autonomy to local governments in spending and managing their revenues. The local governments have the authority to explore and collect their own-source revenue ('Pendapatan Asli Daerah', or PAD), i.e. through the improvement of their tax effort. The objectives of this study are: (i) to describe the fiscal performance of districts and municipalities in Indonesia, both in the revenue as well as the expenditure sides, (ii) to analyze the effects of intergovernmental transfers ('dana perimbangan', or balancing fund from the central to regional governments) on regional tax efforts, and (iii) to identify the regional economic growth elasticity of intergovernmental transfers and own-source revenue. This study employs a panel datasetof 336 districts and municipalities covering the whole area of Indonesia over the time period of 2001-2008. The results show a relatively low contribution of PAD to regional revenues, indicating high fiscal dependency of regional govemments on the central government. Intergovernmental transfers positively effect tax efforts. The re·sult of the elasticity analysis also indicates a positive role of the transfers as stimuli to economic growth.